How do Phytophthora spp. de Bary kill trees? - Davison, Elaine (Scion, 2011)
Phytophthora spp. de Bary are being increasingly recognised as pathogens that cause tree death, without necessarily having any clear understanding of how this happens. Suggested mechanisms include: extensive fine-root necrosis especially on wet or drought prone sites, leading to reduced water uptake, crown decline and death, e.g. Phytophthora quercina T. Jung infection of European oaks; root and stem cankers resulting from phloem invasion and cambial death, leading to death of basal buds and carbon starvation of the root system, e.g. Phytophthora alni Brasier & S.A. Kirk infection of alders; xylem invasion, leading to reduced conduction, hydraulic failure and death, e.g. Phytophthora ramorum Werres, De Cock & Man in ‘t Veld infection of tanoaks; and hormonal imbalance and/or damage from toxins, e.g. Phytophthora cinnamomi Rands infection of eucalypts. These possible mechanisms are reviewed, together with different hypotheses of why trees die, and the predisposing environmental stresses that contribute to tree death. Extensive xylem invasion provides a mechanistic explanation of how death occurs, but is the least frequently reported symptom of Phytophthora infection.